Modellbasierte Analyse des Interferenzverhaltens von Kfz-Radaren - Schipper, Tom (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2017)
The growing number of automotive radars asks for an investigation of their mutual interference. The present work contributes to this research area by providing models and subsequent analyses. The impact of interference on the functionality of radar sensors is discussed on the basis of a virtual test drive and selected scenarios. Furthermore a proposal for the combined use of interference countermeasures is given.